Mother Tongue, Mother's Influence: Exploring Language Choices in Pakistani Famalies in KSA - Hadiqa Malik (JISR Management and Social Sciences & Economics)
A child's language development is a dynamic and intricate process that starts at a very young age and lasts the entirety of their lives. The objective of this paper is to investigate how parents' attitudes and roles affect their children's exposure to their mother tongue. It aims to shed light on whether Punjabi and Urdu are preserved or shifted in the Kingdom of Saudi Arabia. A phenomenological qualitative research approach is used in the current study. Besides, this study employs Fishman's Domain Theory to examine Punjabi speakers' attitudes and language use in Saudi Arabia. By employing snowball sampling, the data has been collected from three Pakistani families residing in Saudi Arabia for more than six years. Findings reveal that mothers believe that learning and speaking multiple languages is crucial for children, but they also believe that sometimes their children blend languages together, so they would rather concentrate on one at a time. Although mothers in Saudi Arabia prefer to speak English and Urdu fluently, their children know Punjabi language and to some extent, they understand it but are not fluent in Punjabi. This study, therefore, recommends various strategies that Pakistani women ought to devise in order to preserve their native language.